DETERMINATION OF ACTIVITY COEFFICIENTS OF NEUTRAL SPECIES IN SUPERCRITICAL H2O SOLUTIONS - Walther J.V. (My University, 1997)
Based on a standard state of unit activity of the solute in a hypothetical one molal solution where activity coefficients are taken as unity at infinite dilution at all pressures and temperatures, the activity coefficients of neutral species generally increase with increasing ionic strength at 25°C. However, activity coefficients of polar species begin to decrease with increasing ionic strength as temperature increases in supercritical aqueous solutions. The increased stability of polar neutral ion pairs helps explain the increase in the solubility of silicate minerals in supercritical aqueous solutions as electrolyte concentrations increase. This is demonstrated for measurements of talc plus quartz solubility in supercritical aqueous NaCl solutions. Increased ion association to form new species in supercritical solutions beyond the formation of neutral ion pairs is, apparently, not important for understanding mineral solubilities in most crustal aqueous solutions.